Disabilità e Behinderung nelle risorse lessicografiche, nella “Legge-quadro per l’assistenza, l’integrazione sociale e i diritti delle persone handicappate” (legge 5 febbraio 1992 n. 104) e nel “Bundesteilhabegesetz” (BTHG) - Flinz, Carolina; Mollica, Fabio (Linguistik Online, 2024)
The aim of this work is an intra- and interlinguistic reflection on the expressions relating to the semantic field of DISABILITY in the main Italian and German lexicographic resources as well as in the two laws regulating and guaranteeing the right to participation of disabled people and promoting their integration in Italy and Germany, respectively (the “Legge-quadro per l’assistenza, l’integrazione sociale e i diritti delle persone handicappate” of the 5th february 1992 n. 104 and the “Gesetz zur Stärkung der Teilhabe und Selbsbestimmung von Menschen mit Behinderungen”). First, the general and specialised Italian and German monolingual lexicographic resources will be taken into account in order to draw preliminary conclusions concerning the lexicographical landscape (Section 2). After a description of the theoretical framework, the use of these expressions in the two legislative texts will be analysed by means of corpus linguistic tools. In particular, the focus will be put on the most frequent and most typical lexemes of the two compiled corpora (LQH and BTHG) and a selection of those will be examined according to their collocational structures (Section 3). As a result, a general picture of terminology related to the sematic field of disability in both languages will be given and contrastive reflections, serving as a starting point for subsequent and broader analyses, will be formulated.